2006
DOI: 10.1089/ars.2006.8.681
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts of Redox Signaling in the Lungs

Abstract: In the intracellular redox state (GSH/GSSG) the cell plays a key role in the regulation and potentiation of the inflammatory response in lung cells. Glutathione and thioredoxin are the important protective antioxidants in the lungs. Regulation of intracellular redox glutathione and thioredoxin levels in response to reactive oxygen/nitrogen species and in inflammation should have critical effects on different lung cells on the activation of redox sensor/signal transduction pathways and various transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 88 publications
0
45
0
Order By: Relevance
“…Inflammation causes enhanced reactive oxygen species (ROS) production and decreased GSH levels, resulting in upregulation of both pro-inflammatory and antioxidant genes (35). Transcription factors that regulate proinflammatory cytokines and chemokines are sensitive to GSH levels, and GSH depletion enhances pro-inflammatory signaling in the alveolar epithelium (19,36). Our data in LPS/ RA mice indicated that lung GSH levels were significantly decreased at 24 h of exposure (36 h after LPS administration) but recovered by 72 h (84 h after LPS administration).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation causes enhanced reactive oxygen species (ROS) production and decreased GSH levels, resulting in upregulation of both pro-inflammatory and antioxidant genes (35). Transcription factors that regulate proinflammatory cytokines and chemokines are sensitive to GSH levels, and GSH depletion enhances pro-inflammatory signaling in the alveolar epithelium (19,36). Our data in LPS/ RA mice indicated that lung GSH levels were significantly decreased at 24 h of exposure (36 h after LPS administration) but recovered by 72 h (84 h after LPS administration).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is often defined as an imbalance between ROS production and antioxidant defenses. Oxidative stress can dysregulate cell signaling (158) and is a potential target for the development of therapeutics to treat lung fibrosis (110).…”
Section: Pathogenesismentioning
confidence: 99%
“…Redox signaling pathways have been shown to play a key role in the activation of inflammatory cascades in the lung (37,44). For example, hydrogen peroxide (H 2 O 2 ) has been reported to mediate IL-1␤ (18) and TNF-␣ (8,20) receptor signaling cascades.…”
mentioning
confidence: 99%